Modified Morley Element Method for a Fourth Order Elliptic Singular Perturbation Problem (Journal of Computational Mathematics, 2006)
This paper proposes a modified Morley element method for a fourth order elliptic singular perturbation problem. The method also uses Morley element or rectangle Morley element, but linear or bilinear approximation of finite element functions is used in the lower part of the bilinear form. It is shown that the modified method converges uniformly in the perturbation parameter.
Keywords: Morley element; Singular perturbation problem.